Anthropology and Health: Organ transplantation from an anthropological perspective. - España Bustos, Andrés Roberto (2020)
Organ transplantation reaches a wide field of study that goes from principles such as solidarity and altruism,legal and regulatory provisions, until the construction of the subjectivity that people adopt by harboring anotherorgan inside your body. This article seeks to expose two anthropological considerations related to organtransplantation: first, a conceptual description of the gift theory proposed by Marcel Mauss (2009) and its relationshipwith transplantation; and in a second moment, the importance of the analysis and the approach ofbiopolitical technology in the biomedical technique of transplantation.